Energy System Planning Considering Renewables and Pumped-storage Power Plants - Costa, Jonas Carvalheira; Bortoni, Edson da Costa; Vieira, Paulo Alberto Viana; Faria, Victor Augusto DurÃƒÂ£es (Department of Electrical Engineering, National Institute of Technology Malang - INDONESIA, 2017)
Renewables  will  play  an  important  role  in  the generation for the next decades, but the great problem they face is the intermittency of the natural resource availability, mainly when considering  solar  and  wind  generation.  In  this  context,  the pumped-storage finds a great opportunity. Its operation consists of two mains mechanisms: to pump water to be stored in an upper reservoir when  there  is  surplus  of energy  in the system,  and  to generate as a regular power plant, with the stored water, when there  is  a  lack  of  energy  in  the  system.  This  paper  presents  an introductory  with  a  revision  of  the  world  consumption  and capacity  of  2030  considering  the  parcel  of  renewables,  and  a simulation  of  several  possibilities  of  the  energy  mix  in  various Scenarios.  The  simulations  consider  mainly  the  contribution  of pumped-storage  hydro.  The  possible  arrangements  of construction  pumped-storage  hydro,  costs,  and  a  mathematical model of linear optimization using pumped-storage are analyzed and  presented.  The  developed  method  is  applied  to  several Scenarios and the conclusions are obtained from that.